2019
DOI: 10.15282/jmes.13.1.2019.17.0387
|View full text |Cite
|
Sign up to set email alerts
|

Cutting tool wear progression index via signal element variance

Abstract: This paper presents a new statistical-based method of cutting tool wear progression in a milling process called Z-rotation method in association with tool wear progression. The method is a kurtosis-based that calculates the signal element variance from its mean as a measurement index. The measurement index can be implicated to determine the severity of wear. The study was conducted to strengthen the shortage in past studies notably considering signal feature extraction for the disintegration of non-determinist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…From the Table 7, it can be concluded that feed has the highest statistical significance followed by 'V' while parameter'd' was discover less effect on Ra. This shows acceptable concurrence with Auici et al [3], D'Mello et al [21] and Boy et al [25]. The interactions V×f has statistical and physical significance on Ra.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…From the Table 7, it can be concluded that feed has the highest statistical significance followed by 'V' while parameter'd' was discover less effect on Ra. This shows acceptable concurrence with Auici et al [3], D'Mello et al [21] and Boy et al [25]. The interactions V×f has statistical and physical significance on Ra.…”
Section: Resultssupporting
confidence: 88%
“…The conventional processes for turning hardened steel are electricdischarge and grinding; and are in limited is use due to high tooling cost, low surface finish and material removal rate, faster wear. To overcome these drawbacks, these materials are turned with the super-hard cutting tools and process is referred as hard turning [3][4]. It is reported that this process is performed with no cooling media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar methods are being developed over the past 10 years at the Universiti Kebangsaan Malaysia from various researchers. They use the standard deviation of a force signal and its higher-order statistical measures (skewness and kurtosis) to calculate a tool wear indicator [10][11][12][13]. Fussel et al also use the force signal to calculate the coefficients of a force model.…”
Section: State Of the Artmentioning
confidence: 99%
“…Productive processing of billets of alloy steels, which are used in large volumes in all industries, is also an urgent task. Reduction deadlines manufacturing products engineering in a lot associated with a raise performance milling planes, edges, chamfers for welding and other parts that are in parts durable titanium ship hull [2]. A significant part of the total volume of milling occurs in extreme conditions -on the scale, with large cross section of cut.…”
Section: Introductionmentioning
confidence: 99%